2004
DOI: 10.1524/ract.92.4.369.35580
|View full text |Cite
|
Sign up to set email alerts
|

Ultratrace and isotope ratios analyses of some radionuclides by ICP-MS

Abstract: Extensive work is under way using High Resolution-ICP-MS for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The precision for 240 Pu/ 239 Pu depends on the level of Pu in the sample. Our results for the isotopic ratios 240 Pu/ 239 Pu are in good agreement with previously published data for IAEA-375, 22 while for SRM-4354 our results are in fair agreement with the results published by Helal et al 24…”
Section: Methods Validation and Analytical Performancessupporting
confidence: 93%
“…The precision for 240 Pu/ 239 Pu depends on the level of Pu in the sample. Our results for the isotopic ratios 240 Pu/ 239 Pu are in good agreement with previously published data for IAEA-375, 22 while for SRM-4354 our results are in fair agreement with the results published by Helal et al 24…”
Section: Methods Validation and Analytical Performancessupporting
confidence: 93%
“…Al-Hamarneh et al (2003) measured the activity concentration of 40 K, 134 Cs, 137 Cs, 90 Sr, 241 Am, 238 Pu and 239þ240 Pu in surface and core soil samples collected from different regions of Jordan. Helal et al (2004) reported that the 90 Sr/ 86 Sr and 240 Pu/ 239 Pu isotope ratios measured in soil samples collected near nuclear facilities confirm that the source of 90 Sr and Pu is global fallout. Al-Meer et al (2013) reported a baseline for 90 Sr in Qatari soils.…”
Section: Introductionmentioning
confidence: 87%
“…Operating under cold plasma can greatly reduce the ionization efficiency of Zr by HR-ICP–MS [ 33 ]. The isotope ratio of 90 Sr/ 86 Sr in soil samples near the nuclear facility was 6.02 × 10 −9 , basically reaching the sensitivity of radiochemical method for the determination of 90 Sr [ 20 ].…”
Section: Measurement Methods Of 239 Pu 2...mentioning
confidence: 99%
“…HR-ICP–MS is also mostly used when measuring the concentration of 239,240 Pu in the environment. Helal et al [ 20 ] measured the isotope ratio of 240 Pu/ 239 Pu of 0.17 in the soil near nuclear facilities. Stefan et al [ 92 ] used the ultrasonic atomization method to measure the Pu isotope activity and 240 Pu/ 239 Pu isotope ratio in environmental samples, with the measurement accuracy (RSD) of the ratio of 240 Pu/ 239 Pu at about 2%.…”
Section: Measurement Methods Of 239 Pu 2...mentioning
confidence: 99%
See 1 more Smart Citation